Negotiating Discourses: A Pākehā Teacher Educator’s Exploration of Bicultural Teaching Practice - Alison Warren (New Zealand Journal of Teachers' Work)
Bicultural teaching practice in Aotearoa New Zealand is based on commitment to partnerships reflecting Te Tiriti o Waitangi/ The Treaty of Waitangi between Māori and non-Māori cultures, and is governed by professional standards and documents. I am a Pākehā (European ethnicity) early childhood teacher educator concerned about how effectively I engage in bicultural teaching practice. According to Michel Foucault’s theories, individuals’ self-understandings are shaped within discourses that frame their values and beliefs, and their thoughts and actions. This article reports on poststructural self-study research into my negotiations within three discourses of bicultural teacher education practice, as well as discourses of colonisation that continue to pervade Aotearoa New Zealand.